Cathode materials with cross-stack structures for suppressing intergranular cracking and high-performance lithium-ion batteries. (20th January 2018) - Chen, Xianglei; Li, De; Mo, Yan; Jia, Xiaobo; Jia, Jianfeng; Yao, Chao; Chen, Daming; Chen, Yong
Abstract: Full concentration-gradient Li[Ni0.6 Co0.2 Mn0.2 ]O2 (FCG622) layered oxide cathodes, consisting of Ni-rich cores and concentration-gradient shells, were synthesized by heterogeneous co-precipitation method. The cross-stack structure of FCG622 appeared different from the polycrystalline aggregates of homogeneous Li[Ni0.6 Co0.2 Mn0.2 ]O2 (H622). The FCG622 showed structural stability and excellent electrochemical performances when compared to H622. The cathode based on this material showed superior rate capability and high voltage performance. The results of charge and discharge testing illustrated that FCG622 could suppress the intergranular cracks delivering initial discharge capacity of 185.2 mAh g −1 at 1C in the voltage window of 2.8–4.4 V. The corresponding capacity retention after 300 cycles was estimated to 81.1% at 4.4 V. By comparison, the initial discharge capacity of H622 was estimated to only 170.6 mAh g −1 under the same conditions, with capacity retention of 68.5%.These results suggested that FCG622 had stable morphology, high capacity and superior voltage stability when compared to polycrystalline aggregates.